Data Mining Approach tool in Fishing Control Activity - Ferreira, J. (IMAM 2017, 2017)
In this research work is described about an implemented process to control the fish type and weight in order to achieve the identification of non-compliant data reports. Such process is based in a mining model using Artificial Intelligence (AI) settings, namely based on data mining approaches of Naïve Bayes and Decision Trees. We identify fishing patterns based on past data, crossing Vessel Monitor System (VMS) data, with fishing reports (DPE), created by vessel master. Thus, it allows to identify possible non-conforming fishing report based on deviations from the patterns derived from the training mining model. We use real data from Portuguese fishing activities.